2017
DOI: 10.1097/pai.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinicopathologic Parameters and Survivals Between Epstein-Barr Virus–positive and Her2-positive Gastric Cancers

Abstract: Gastric carcinomas are highly mortal neoplasms for which new therapeutic options are being searched. The molecular subtyping of gastric adenocarcinomas was proposed recently, and the relationship between etiopathogenetic types is still under investigation. Here we compared histopathologic, prognostic, and survival differences between Epstein-Barr virus (EBV)-positive and Her2-positive gastric adenocarcinomas. In a retrospective design, we searched the EBV status with Epstein Barr Virus encoded small RNA (EBER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
5
14
1
Order By: Relevance
“…One study has found significantly less high HER2 expression in EBV positive cases than in EBV negative (5% versus 24%; p < 0.001) and has suggested that LMP2A may suppress the HER2 expression [20]. Other studies have also found a negative correlation between EBV and HER2 positivity [21,22]. One study has found a slightly higher HER2 expression in EBV positive GC cases (7%) than described in other reports [23].…”
Section: Discussionmentioning
confidence: 90%
“…One study has found significantly less high HER2 expression in EBV positive cases than in EBV negative (5% versus 24%; p < 0.001) and has suggested that LMP2A may suppress the HER2 expression [20]. Other studies have also found a negative correlation between EBV and HER2 positivity [21,22]. One study has found a slightly higher HER2 expression in EBV positive GC cases (7%) than described in other reports [23].…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, the estimated EBV positive rate was 11.3%. EBV positive rates ranged from 1.2% to 89.2% in the individual eligible studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, EBV positivity has been significantly correlated with some clinicopathological characteristics, sex, and tumor location [ 22 , 26 , 53 ]. In the present study, there was a significant correlation between EBV positivity and the patient’s sex; however, EBV positivity was not correlated with lymphovascular invasion or pTNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there are some histopathological features of ERBB2+ GC ( Park et al, 2016 ). ERBB2 positivity is more often observed in intestinal-type GC ( He et al, 2013 ; Irkkan et al, 2017 ). Up-to-date, there is no correlation analysis on both levels of genomics and clinical histology for ERBB2+ GC.…”
Section: Discussionmentioning
confidence: 99%